Apresentação da Seção Temática – Educação e Relações Étnico-Raciais - Meinerz, Carla Beatriz; Pereira, Júnia Sales (Educação & Realidade, 2016)
Apresentação da Seção Temática – Educação e Relações Étnico-Raciais